2016
DOI: 10.1111/jicd.12224
|View full text |Cite
|
Sign up to set email alerts
|

Impact of bleaching agents on water sorption and solubility of resin luting cements

Abstract: Sorption and solubility behavior of the studied cements were highly correlated and significantly affected by applying either office or home bleaching agents; seT showed the highest sorption and solubility, whereas Rely X Unicem revealed the lowest.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
6
0
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 20 publications
(42 reference statements)
2
6
0
1
Order By: Relevance
“…In the current study, cola did not create as much discoloration as coffee in any of the materials, although it has a lower pH 2.5, which is potentially more deleterious than coffee (pH 5.4). The reason could be the yellow colorants in coffee that are absorbed in the body of the materials and penetrate into the organic phase of the materials . In agreement with the results of our study, coffee has been reported as the most severe staining drink in other studies .…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…In the current study, cola did not create as much discoloration as coffee in any of the materials, although it has a lower pH 2.5, which is potentially more deleterious than coffee (pH 5.4). The reason could be the yellow colorants in coffee that are absorbed in the body of the materials and penetrate into the organic phase of the materials . In agreement with the results of our study, coffee has been reported as the most severe staining drink in other studies .…”
Section: Discussionsupporting
confidence: 92%
“…For instance, the highest Ra value for Rok was shown in coffee, while for Filtek Z250, it was observed in cola. Because roughness is a surface property, it is affected by water sorption, which is a complex phenomenon and is dependent on the matrix resin, filler, and interfacial bonding between particles and matrix . Decreased filler loading has been shown to result in greater water absorption .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For instance, the highest Ra values for Z250 and 4 Seasons were shown for acidic solutions. Because roughness is a surface property, it is affected by water sorption, which is a complex phenomenon dependent on the matrix resin, filler, and interfacial bonding between the particles and the matrix [19,20]. Decreased filler loading has been shown to result in greater water absorption.…”
Section: Discussionmentioning
confidence: 99%
“…Bu etki ise kahve içerisindeki daha az polar özellikte olan renklendiricilerin kompozit içerisine derin bir şekilde penetre olmasıyla açıklanmıştır (25). Kahve içerisindeki bu sarı renklendiriciler rezin kütlesi tarafından absorbe edilip organik matriks içerisine penetre olarak renklenmeye sebep olmaktadırlar (26). Bu çalışmada da beyazlatma sonrası bu pigmentler oksidasyona uğradıkları için renk değişiminin kahvede bekletilen örneklerde bu kadar fazla olduğu kanaatindeyiz.…”
Section: Malzeme/ Kısaltması Türü İçeriğiunclassified